تفعيل دور مدير المدرسة الثانوية العامة في تنمية الأداء المهني للمعلمين بمصر على ضوء القيادة التنموية - هلال، محمد سعيد عبدالمطلب; محمود، بدرية مصطفى (الجمعية المصرية للتربية المقارنة والإدارة التعليمية, 2023)
تسعى القيادة الفعالة إلى تنمية أداء معلميها المهني، وتدفعهم نحو ذلك بالشكل والطريقة التي تمكنهم من ذلك، خاصة وأن أداء المعلمين لا يتوقف على مقدرتهم الذاتية وحسب، وإنما يتوقف بدرجة كبيرة على عوامل وقوى إيجابية تتوافر في المناخ المدرسي، فهم بحاجة إلى الشعور بأن لديهم تأثير في البيئة المدرسية وأنهم يشاركون في اتخاذ القرار، ويتطلب ذلك أن يتولى إدارة المدرسة الثانوية قيادات تربوية واعية على قدر عالي من الكفاءة والفاعلية، وتتعدد أنماط القيادة التي توثر في المناخ المدرسي بصفة عامة، والأداء المهني للمعلمين بصفة خاصة ويأتي ضمن هذه الأنماط القيادة التنموية. وتهتم القيادة التنموية بتزويد المعلمين بالمعارف والمهارات والفرص والإجراءات الجديدة، من خلال ممارساتها المتنوعة من توجيه وإشراف ومتابعة وإرشاد، وتقديم التغذية الراجعة للأداء، وتحديد الاحتياجات التدريبية للمعلمين، وتوفير الفرص والظروف التي تساعد المعلمين على تحسين وتطوير وتنمية أدائهم، والعمل بشكل أكثر فاعلية بما ينعكس على أداء المعلمين والمدرسة ككل ويحقق تميزها ويجعلها قادرة على المنافسة حيث أن المؤسسة التعليمية لا تستطيع تحقيق ميزة تنافسية ما لم يعمل المعلمين بها باستمرار عند مستويات الأداء العالي. هذا ويتمحور الهدف الرئيس من هذا البحث في الإجابة عن السؤال الرئيس التالي: كيف يمكن تفعيل دور مدير المدرسة الثانوية العامة في تنمية الأداء المهني للمعلمين بمصر على ضوء القيادة التنموية؟ وانطلاقا من طبيعة البحث، ومشكلته، وتحقيقا لأهدافها، فإن البحث الحالي يعتمد على منهج الوصفي، ويستعين البحث باستمارة لاستطلاع آراء خبراء الإدارة التربوية والتخطيط حول القائمة المقترحة لأدوار مديري المدارس الثانوية العامة بمصر في تنمية الأداء المهني للمعلمين على ضوء القيادة التنموية. هذا وقد توصل البحث إلى القائمة المقترحة لأدوار مديري المدارس الثانوية العامة بمصر في تنمية الأداء المهني للمعلمين على ضوء القيادة التنموية، واقترح مجموعة من الإجراءات لتفعيل دور مدير المدرسة الثانوية العامة في تنمية الأداء المهني للمعلمين بمصر على ضوء القيادة التنموية. The effective leadership seeks to developing the professional performance of its teachers, as it pushes them to achieve that by using the appropriate way to be able to achieve that goal, especially because teachers’ performance couldn't be limited at their self- capabilities only, but it includes many positive factors, and forces that are found greatly at the school climate, as they need to feel that they can affect the school environment, and also the can participate in decision making, the matter that requires awakened, effective, qualified, and educational secondary school leaders, in general, there are many leadership patterns that can affect the school climate, and especially, there are patterns that can affect the professional performance, the developmental leadership is one of these patterns. Developmental leadership is interested in providing teachers with knowledge, skills, opportunities, and also the new procedures, through its various practices, such as: guidance, supervision, following up, introducing feedback about performance, identifying teachers' training needs, providing opportunities and circumstances that can help teachers in improving, and developing their performance, in order to work more effectively, the matter that is reflected on teachers' performance, and the school as a whole, to accomplish its distinguished position, to be able to compete other schools, as the educational institution can't achieve competitive advantage, if teachers won't work continually to reach high levels of performance. The main objective of this research is to answer the following main question: How can the general secondary school principal role be activated in developing teachers' professional performance in Egypt in the light of the developmental leadership? Based on the nature of the research, its problem, and in order to achieve its objectives, the current research relies on the descriptive approach, and the research uses a form to solicit the views of educational administration and planning experts on the proposed list of the roles of principals of public secondary schools in Egypt in developing the professional performance of teachers in the light of developmental leadership. The research reached a proposed list of the roles of public secondary school principals in Egypt in developing the professional performance of teachers in the light of developmental leadership and suggested a set of measures to activate the role of the principals of public secondary schools in developing the professional performance of tea chers in Egypt in the light of developmental leadership.
Keywords: المدارس المدرسية -- القطاع الثانوي -- الإداء المدرسي -- القيادات التربوية -- التنمية المهنية -- الأهداف التنموية